Klasifikasi Status Gizi Balita Menggunakan Metode Naive Bayes Di Puskesmas Sawah Lebar Kota Bengkulu - Agri Ayu Dewani; Herlina Latipa Sari; Eko Suryana (Jurnal Media Infotama, 2025)
Toddler is an abbreviation for babies under five years old, a time when the child's brain experiences rapid growth. Nutrition is actually the most important thing because it is related to human health itself, especially toddlers. In general, toddlers are very vulnerable to nutritional status problems. Therefore, the growth and development of toddlers is an important concern for parents. Classification of nutritional status of toddlers using the Naïve Bayes method at the Sawah Lebar Health Center, Bengkulu City, can help in determining the level of health and make it easier to determine the nutritional status of toddlers so as to provide appropriate and necessary interventions to prevent or overcome nutritional problems in toddlers, and facilitate the classification process to solve problems in large amounts of data using the Naïve Bayes method. Based on testing data in the February Period of 2025, the results obtained are 4 toddlers into the classification of good nutritional status, 3 toddlers into the classification of malnutrition status, and 2 toddlers into the classification of risk of overnutrition. The results of this classification can then be used as a reference for medical personnel at the Bengkulu City Sawah Lebar Health Center to provide appropriate and necessary interventions to prevent or overcome nutritional problems in toddlers.